FRI0038 Vitamin D Serum Level in Early Arthritis Patients: Association with Disease Activity, Disability and Severity in the Espoir Cohort. (9th June 2015) - Gamon, E.; Mouterde, G.; Lukas, C.; Orsini, M.; Seror, R.; Combe, B.
Abstract : Background: Environmental factors may play a crucial role in auto-immune diseases. Besides tobacco, other factors like vitamin D are suspected to impact the onset and the subsequent activity of inflammatory arthritis including rheumatoid arthritis (RA), but its association with severity of the disease has not been evaluated yet. Objectives: To examine the association of baseline vitamin D serum level with RA severity, disability, disease activity, response to treatment over the first year in early arthritis patients. Methods: Patients presenting with synovitis of at least 2 joints for 6 weeks to 6 months were included in the multicenter French ESPOIR cohort. 25OH vitamin D2 and D3 was measured at baseline and then separated into 3 groups: deficiency (<10 ng/ml), insufficiency (10-30 ngl/mL), normal level (≥30ng/mL). Correlation between vitamin D levels and DAS28, HAQ and van der Heijde modified total Sharp score (mTSS) were assessed at baseline by a Spearman correlation analysis. Bivariate analyses of the association between baseline vitamin D level and other outcomes were conducted: radiographic progression defined by an increase of at least 1 point of the mTSS at 12 months; disability (defined by an HAQ≥1); disease activity (DAS28) and RA diagnosis (2010 ACR/EULAR criteria) at baseline, 6 and 12 months; response to treatment (EULAR response) at 6 and 12 months. Forward stepwise multiple logistic regression was used to evaluate independent association between baseline variables and formerly described outcomes. Results: Among 813 patients included in the cohort, 810 were analyzed and 138 (16.97%), 522 (64.21%), 150 (18.45%) had vit D<10, 10-30 and ≥30ng/mL respectively. Vitamin D levels were found to be correlated with DAS28, mTSS and HAQ at baseline (Rho=-0.11, p=0.0016; Rho=-0.07, p=0.0335 and Rho=-0.11, p=0.0016 respectively). In bivariate analyses, patients with vitamin D deficiency had more radiographic progression at 12 months compared to vitamin D normal group (OR=1.82 95% CI 1.05-3.15, p=0.0323). Patients with a HAQ ≥1 were more frequent in deficiency group compared to normal group at baseline and 6 months (OR=1.89 95% CI 1.18-3.03, p=0.008 and OR=2 95% CI 1.15-3.49 p=0.0146 respectively). Patients with DAS28>5.1 were more frequent in deficiency group compared to normal group at baseline (OR=1.84 95%CI 1.15-2.87 p=0.011). There was no link between vitamin D level and RA diagnosis at baseline, 6 and 12 months nor with response to treatment at 6 and 12 months. In multivariate analysis, radiographic progression at 12 months was associated with vitamin D deficiency (OR=1.95 95% CI 1.05-3.62, p=0.038), age, ACPA, CRP, alcohol consumption and season of onset. Likewise, disability at baseline was associated with vitamin D deficiency (OR=1.73 95% CI 1.05-2.85, p=0.03), age, CRP, corticosteroid use and disease duration; disability at 6 months was associated with vitamin D deficiency (OR=2.01 95% CI 1.15-3.52, p=0.025), age and sex. Conclusions: Vitamin D deficiency may be predictive of radiographic progression at 1 year and is associated with increased disability at baseline and 6 months in early arthritis patients. These data reinforce the role of environmental factors in the development and outcome of RA. Disclosure of Interest: None declared